Effectiveness of Full Length and Cut Percutaneus Nephrostomy in Pediatrics Population - Tariq Ahmad, Sohail Shabbir, Muhammad Asif Ammar, Fazal Manan, Muhammad Rashid Jamal, Zarmast Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Purpose of the study is to evaluate the safety and efficacy of full length Percutaneous (PCN) versus cut PCN in pediatric population. PCN is performed to establish temporary drainage of obstructed or dilated renal system till definitive management. PCN is well established procedure which is performed under deep sedation, local anesthesia or general anesthesia ultrasound guided or fluoroscopic guided. Methodology: Randomized controlled study carried out in 200 children in the department of urology, Institute of Kidney Disease, Hayatabad Peshawar Pakistan from Jan 2020 to Apr 2022 and analysis was done by using SPSS version 20 to know the efficacy of the cut versus full length PCN in children. Results: This study was carried out over 200 children using cut and full length percutaneous nephrostomy tube, 100 in each group. This study includes 119 males and 81 females of mean age 5.49+ 3.127 years. The cause of obstruction was 61% PUJ obstruction, 55% VUR, 47% obstructed stone and other causes in 37%patients. Effective decompression of hydronephrosis were noted in 89% in cut length vs 82% in full end PCN (p<0.1%). Skin inflammation of 100% with cut end PCN and 20% with full length, 96% of PCN didn’t show any inflammation (p<0.001%). Dislodgment of PCN was noted multiple time in 54%, two times in 38% and 7% in full length PCN where as it is noted two times in 47% and one times in 45% in cut PCN(p<0.001%). PCN exchange was needed multiple times in 51% patients and two times in 39% patients in full length PCN where it was needed two times in 41% and one time in 50% patients in CUT PCN arm (0.001%). Conclusion: This study concludes that cut end PCN is more effective in term of PCN exchange and dislodgement but having more skin inflammation as compared to full length PCN